Ellipsometric plasmon sensor for adsorbed layers on thin Ag and Au films - Severynov, V.L.; Shaikevich, I.A.; Shybiko, Y.A. (Functional Materials, 2005)
Using Kretschmann’s method, important parameters defining the propagation of surface waves (namely, the restored polarization azimuth ψ and phase difference Δ between p- and s-components of the electromagnetic wave) versus the light incidence angle θ for thin Ag and Au films have been investigated. It has been show that at wavelength λ = 620 nm, the ellipsometric sensor on Au film is more sensitive to molecular pollutions than sensor on Ag film.